ANALYSIS OF THE RPP OF THE QUR'AN AND HADITH AS A MEANS OF STRENGTHENING ISLAMIC EDUCATION VALUES IN GRADE III MI AL-IHSAN - Siti Salwa Yusyifa; Muhammad Ramli (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the Lesson Implementation Plan (RPP) for the Al-Qur'an Hadith subject for grade III MI as a means of strengthening Islamic educational values. This study is motivated by the reality that learning the Al-Qur'an Hadith often only emphasizes cognitive aspects, such as memorization and literal understanding, without integrating spiritual and moral values as a whole in learning planning. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and document analysis. The results of the study indicate that although the RPP has included elements of Islamic values, its integration is still implicit. Learning objectives tend to be cognitive, teaching methods are still predominantly lectures, conventional learning media, and the assessment system is more focused on written test results. It is necessary to develop a more innovative and contextual RPP by emphasizing active, reflective, and value-based learning. This study recommends increasing teacher capacity through ongoing professional training so that learning the Al-Qur'an Hadith is able to answer the challenges of character education in the modern era.